Synthesis and self-assembly of temperature-responsive copolymers based on N-vinylpyrrolidone and triethylene glycol methacrylate1. Issue 22 (14th June 2015) - Jumeaux, Coline; Chapman, Robert; Chandrawati, Rona; Stevens, Molly M.
<x xml:space="preserve">Abstract</x> Synthesis of well-defined block copolymers of PVP-co-pTEGMA from a dual RAFT/ATRP CTA and study of their temperature-responsive properties driving self-assembly.